The Digital Economy, ICT and Economic Growth in the CEE Countries - Arendt, Łukasz (Olsztyn Economic Journal, 2015)
This paper focuses on the relationship between Information and Communication Technologies, GDP growth and productivity in the Central and Eastern European (CEE) countries. It elaborates on measures of the digital economy/information society, emphasizing the role of complementary factors to ICT that are crucial for the productive use of these General Purpose Technologies. The paper discusses the impact of technical progress, induced by the development of ICT, on sources of economic growth by describing changes in the contribution of ICT capital and non-ICT capital, labour and TFP to GDP growth in the CEE and EU-15 countries.